1989
DOI: 10.1017/s0016672300028652
|View full text |Cite
|
Sign up to set email alerts
|

Restriction map and α-amylase activity variation amongDrosophilamutation accumulation lines

Abstract: SummaryThe specific activities of α-amylase were measured for two sets of mutation accumulation lines, each set having originated from a different lethal-carrying second chromosome and SM1(Cy) chromosome and having been maintained by a balanced lethal system for about 300 generations. Significant variation was found to have accumulated among lines of both sets. Because of dysgenic crosses in the early generations of mutation accumulation, insertions or deletions of transposable elements in the Amy gene region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1990
1990
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
2
1
Order By: Relevance
“…Aquadro et al (1990) confirmed the increased ADH activity variation, and conducted a molecular analysis of a 13-kb Adh gene region. Unlike the results of Tachida et al (1989), no restriction map variation was found. Their restriction mapping analysis showed that the mobilization of transposable elements had not occurred in the Adh gene region in the chromosome lines used.…”
Section: Introductioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Aquadro et al (1990) confirmed the increased ADH activity variation, and conducted a molecular analysis of a 13-kb Adh gene region. Unlike the results of Tachida et al (1989), no restriction map variation was found. Their restriction mapping analysis showed that the mobilization of transposable elements had not occurred in the Adh gene region in the chromosome lines used.…”
Section: Introductioncontrasting
confidence: 95%
“…To understand the mechanisms by which variation is maintained, it is beneficial to study the composition of spontaneous mutations which affect enzyme activity. Tachida et al (1989) examined the restriction map variation in a 14-kb Amy gene region among chromosome lines that showed a significant variation in amylase enzyme activity. They found that the amylase activity variation was caused largely by a genetic change that had occurred in the region of the Amy structural gene.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a fraction of the viability decline observed during the early generations of Ohnishi's experiment could be non-mutational (Keightley, 1996 ;Garcı! a-Dorado, 1997), and could be attributed to an initial increase in the viability of the Cy reference chromosome through variation introduced by gene conversion or double crossingover (Tachida et al, 1989). This phenomenon may also apply to Mukai's experiments.…”
Section: (I) Drosophilamentioning
confidence: 96%